Preliminary data on aquatic insects of Dak Mi Protection Forest, Quang Nam province - Ngo Xuan, Nam (VNU Journal of Science: Natural Sciences and Technology, 2017)
Aquatic insects were investigated from 11 sampling sites in selected waterbodies of Dak Mi Protection Forest in Quang Nam in March, September, 2015 and March, 2016. As the results, a total of 92 species, belonging to 67 genera, 38 families, 8 orders of aquatic insects were recognized here. Among them, the order Ephemeroptera is the most diverse with 26 species (28,26%), followed by the Odonata with 18 species (19,57%), Hemiptera with 13 spieces (14,13%), Tricoptera with 12 species (13,04%). The Coleoptera and Plecoptera have the same diverse with 8 species (8,70%). The Diptera have 6 spieces (6,52%) and the last is Megaloptera has only one species (1,09%). This study has provided the first data of aquatic insects in this area.